ANALISIS FENOMENA PENURUNAN PENERIMAAN PAJAK PADA WAJIB PAJAK UMKM DI KABUPATEN BANDUNG - Lidia Andiani; Ni Wayan Kiki Jayanti Pratiwi Sujana (Jurnal Manajemen Dirgantara, 2023)
This research aims to findout the causes that influence the phenomenon of a decrease in the number of tax revenues of MSME taxpayers at KPP Pratama Badung Selatan in 2018 - 2021. the type of research is qualitative with a phenomenological approach. In this study, researchers used several data collection techniques through: Documentation, interviews with a depth interview approach. Based on the results of the study, the researchers found several factors that influence the phenomenon of a decrease in the amount of tax revenue in the MSME sector as follows: the time limit for utilization of facilities from PP. No.23, the change in tax rates from PP No.46 of 2013 to PP No.23 of 2018, the co-19 pandemic, low taxpayer awareness due to lack of socialization, maximum education carried out by KPP Pratama Badung Selatan and trust in government officials. The contribution of researchers in this study is expected to provide useful information for the KPP Pratama Badung Selatan and the community, as well as MSME taxpayers.